Paraquat Removal from Water by Magnetic Nanoparticles Coated with Waste-Sourced Biobased Substances - Ocampo, Santiago (2024)
The use of biobased substances derived from industrial and household waste as renewable raw materials for environmental applications is gaining prominence due to its sustainable and costeffective approach to waste valorisation. Herein, we report the uptake of paraquat, a widely used pesticide, by magnetite nanoparticles coated with composted urban biowaste-derived substances (MNP-BBS).Themagneticnanoparticleswerepreparedusingamodifiedco-precipitationmethod,and were characterized through various physicochemical techniques. They were tested as an adsorbent for paraquat removal under diverse experimental conditions, exploring the influence of pH (3–10), MNP-BBS dosages (200–1000 mg L−1), ionic strength (0–0.01 M), and presence of organic matter. The kinetic study revealed that the adsorption of paraquat onto MNP-BBS follows the pseudosecond-order model, reaching the adsorption equilibrium after 2 h of contact and 90% of paraquat removal in the best condition tested (1000 mg L−1). The equilibrium experimental data showed a high adsorption performance with a good fitting to the Freundlich isotherm model. Also, from Langmuir model a maximum adsorption capacity of 0.085 mmol g−1 was estimated. The results indicated that electrostatic interaction between the negative functional groups of the adsorbent and the paraquat play a major role in the adsorption mechanism, although the contribution of π-π and hydrophobic interactions cannot be completely ruled out. This research underscores the potential of utilizing MNP-BBS as an effective adsorbent for the removal of paraquat, shedding light on its application in sustainable water purification processes.